2016
DOI: 10.1186/s12970-016-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrolyzed high-pH alkaline water on blood viscosity in healthy adults

Abstract: BackgroundPrevious research has shown fluid replacement beverages ingested after exercise can affect hydration biomarkers. No specific hydration marker is universally accepted as an ideal rehydration parameter following strenuous exercise. Currently, changes in body mass are used as a parameter during post-exercise hydration. Additional parameters are needed to fully appreciate and better understand rehydration following strenuous exercise. This randomized, double-blind, parallel-arm trial assessed the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
5
20
0
2
Order By: Relevance
“…The results of our study are in line with the available literature regarding the impact of alkaline water on blood and urine pH at rest [ 9 , 19 , 25 ]. However, novel results of the present research are related to the changes in HCO 3- after exercise in athletes ingesting alkaline water.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study are in line with the available literature regarding the impact of alkaline water on blood and urine pH at rest [ 9 , 19 , 25 ]. However, novel results of the present research are related to the changes in HCO 3- after exercise in athletes ingesting alkaline water.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained in our study are mostly confirmed in the available literature regarding the use of alkalized water, al-though few studies have been conducted on competitive athletes involved in intense anaerobic exercise [13,14,23] .…”
Section: Discussionsupporting
confidence: 85%
“…The foregoing conclusion was based on research involving blood viscosity tests in a randomised group of 100 adults. Alkaline water decreased blood viscosity by 6.30%, which was significantly more than the result obtained with standard water (3.36%) [14] . Alkaline water may also inhibit the effect of oxidative stress generated in cells during high-intensity exercise.…”
Section: Introductionmentioning
confidence: 52%
“…Those findings are similar to the results of this study, which determined that antioxidative stress rose in those who consumed AEW. Importantly, Weidman et al [ 54 ] stated that the consumption of AEW may exert positive effects by increasing antioxidant defense and reducing the basal production of oxidants after exercise training. Moreover, it was found that AEW has beneficial effects on exercise due to its free radical-scavenging properties, thereby enabling the maintenance of muscle performance and redox homeostasis during consecutive days of exercise [ 29 ].…”
Section: Discussionmentioning
confidence: 99%